HUBUNGAN LEARNING BORNOUT DENGAN BEHAVIOR ACADEMIC CYBERLOAFING PADA PESERTA DIDIK KELAS XII DI SMA N COLOMADU TAHUN 2024/2025 - Geantini Putri, Syifa Nabila; Sri Suryanti, Hera Heru; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
HUBUNGAN LEARNING BORNOUT DENGAN BEHAVIOR ACADEMIC CYBERLOAFING PADA PESERTA DIDIK KELAS XII DI SMA N COLOMADU TAHUN 2024/2025. This study aims to find out whether there is a relationship between Learning Bornout and Behavior Academic Cyberloafing in Grade XII Students at SMA N Colomadu in 2024/2025. The population in this study is 318 students in grade XII of Colomadu State High School for the 2024/2025 Academic Year. In this study, sampling was taken using cluster random sampling. In this study, the sample used was 36 students. Data collection techniques using questionnaires and documentation. The questionnaire method was used to collect data on Learning Bornout and Behavior Academic Cyberloafing, while the documentation method was used to collect data in the form of photos of research activities. The data analysis technique uses product moment correlation. Based on the results of statistical data analysis on the Relationship between Learning Bornout and Behavior Academic Cyberloafing in Grade XII Students at SMA N Colomadu in 2024/2025, an r calculation of 0.859 was obtained. With a value of N = 30, the value of the table is significantly 5% of 0.329 and 1% of 0.424. This indicates that the data analysis obtained r is greater than the t table, which is 0.329 < 0.859. From these results, it indicates that there is a significant positive relationship between Learning Bornout and Behavior Academic Cyberloafing, so this suggests that the higher the Learning Bornout, the higher the Behavior Academic Cyberloafing in grade XII.A2 students of SMA N Colomadu. Conversely, the lower the Learning Bornout, the lower the Behavior Academic Cyberloafing. Based on the results of the study, it can be concluded that Ho was rejected which reads